2015
DOI: 10.7897/2277-4343.06251
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparative Clinical Trial of Swarnmakshika Bhasma and Compound (Swarnmakshika Bhasma and Yashada Bhasma) in the Management of Pandu With Special Reference to Iron Deficiency Anemia

Abstract: Iron deficiency anemia (IDA) is most prevalent nutritional deficiency worldwide. Anemia generally manifests as easy fatigability, exertional dyspnoea, palpitations, body aches and giddiness depending upon its severity, rapidity of onset and underlying pathology. Treatment of iron deficiency anemia mainly involves correction by iron supplementation but constipation, diarrhea, nausea, epigastric discomfort etc. are frequently encountered as side effects during clinical practice. Pandu has been described in Ayurv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It is very much consistent with the results of previous studies conducted by Nagesh CS et al, Meghna V, Abhishek. [28][29][30] The objective parameters viz. Hb%, PCV, MCV, MCH, MCHC, RBC count were also significantly improved after treatment with p<0.001 in both groups.On intergroup comparison p >0.05 showed that there was no statistically significant difference between the two groups suggesting that test drug is as effective as control drug inthe improvement of objective parameters.These results are comparable with the studies conducted by Vaidya Meghna et al 29 Pharmacopeial formulation, "Majunekhabsulhadeed" a jelly form medicinecontains amla khusk, balchar, baheda, peepalkalan, tukhmeshibt, tukhmgandana, zanjabeel, chitalakri, saad kufi, filfilsiyah, halelasiyah, ghee and khabsulhadeed mudabbar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very much consistent with the results of previous studies conducted by Nagesh CS et al, Meghna V, Abhishek. [28][29][30] The objective parameters viz. Hb%, PCV, MCV, MCH, MCHC, RBC count were also significantly improved after treatment with p<0.001 in both groups.On intergroup comparison p >0.05 showed that there was no statistically significant difference between the two groups suggesting that test drug is as effective as control drug inthe improvement of objective parameters.These results are comparable with the studies conducted by Vaidya Meghna et al 29 Pharmacopeial formulation, "Majunekhabsulhadeed" a jelly form medicinecontains amla khusk, balchar, baheda, peepalkalan, tukhmeshibt, tukhmgandana, zanjabeel, chitalakri, saad kufi, filfilsiyah, halelasiyah, ghee and khabsulhadeed mudabbar.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] The objective parameters viz. Hb%, PCV, MCV, MCH, MCHC, RBC count were also significantly improved after treatment with p<0.001 in both groups.On intergroup comparison p >0.05 showed that there was no statistically significant difference between the two groups suggesting that test drug is as effective as control drug inthe improvement of objective parameters.These results are comparable with the studies conducted by Vaidya Meghna et al 29 Pharmacopeial formulation, "Majunekhabsulhadeed" a jelly form medicinecontains amla khusk, balchar, baheda, peepalkalan, tukhmeshibt, tukhmgandana, zanjabeel, chitalakri, saad kufi, filfilsiyah, halelasiyah, ghee and khabsulhadeed mudabbar. 31 The improvement in the subjective and objective parameters seen in the present study as iron oxide per se provides blood iron (Fe) and act as an antioxidant compound, in addition to the supplementary effect of the chemical constituents of the ingredients of majunekhabsulhadeedviz.…”
Section: Discussionmentioning
confidence: 99%